A major practicum report at the Philippine Carabao Center, University of the Philippines Los Banos, B. M. Gonzalez Animal Science Complex College Laguna - Boque, Cheryll Gatmin (2007)
As a major requirement of the Bachelor of Science in Food Technology program, the student completed the 288 hours practicum at the Philippine Carabao Center at University of the Philippines Los Banos, Laguna last April-May 2006. This was aimed at relating the Food Science and Technology concepts and theories to the food processing practices such as food processing, quality and safety as well as learning from the experience and training acquired from the food plant. The student was exposed to the production and physical analyses of raw milk, in-line production of pasteurized fresh milk, chocomilk, pastillas de leche, white cheese, yoghurt, ice cream, as well as research and development of new products. Through the field training, she was able to assess the different processes for raw milk production to marketing of the finished products. Furthermore, the student was able to learn interpersonal relationship skills in dealing with workers in the food plant
Thesis (BS Food Technology) -- University of the Philippines Mindanao, 2007
Keywords: Philippine Carabao Center; Philippine Carabao Center -- U.P. Los Banos, Laguna; Milk; Milk -- Raw; Milk -- Production; Milk -- Packaging; Milk -- Labeling; Milk -- Raw -- Storage